Health-Related Quality of Life Among Adolescent Girls with Idiopathic Scoliosis Using Spinal Orthoses: A Systematic Review - Ellysa Okky Gusma; Gatot Sunarto; Gian Lisuari Adityasiwi; Hana Kristina; Nathan Agwin Khenda (Epidemiology and Society Health Review (ESHR), 2026)
Background: Adolescent idiopathic scoliosis (AIS) affects 2–4% of adolescents and is predominantly diagnosed in girls during pubertal growth. Bracing is the primary conservative intervention to prevent curve progression; however, adolescence is a critical period of psychosocial development, making brace wear particularly burdensome. As evidence-based guidance for holistic management remains limited, this study aimed to review the QoL of adolescent girls with AIS undergoing brace treatment. Method: A literature review was conducted using PubMed and Google Scholar for articles published between 2019 and 2026. Inclusion criteria were adolescents aged 10–18 years with AIS, treated with bracing, and assessed using validated QoL instruments (SRS-22, BrQ, BSSQ). From 1,245 identified records, 15 studies were included following PRISMA-based screening and JBI quality assessment. Results: Brace treatment negatively affects QoL across physical, psychological, and social domains. Patients reported discomfort, limited mobility, body image concerns, emotional distress, and reduced social participation. QoL outcomes were influenced by brace duration, curve severity, and family support. Improved brace design and multidisciplinary care were shown to mitigate these impacts. Conclusion: Bracing significantly affects QoL in adolescent girls with AIS. A patient-centered approach that integrates psychosocial support and improved brace design is essential for enhancing treatment adherence and overall well-being.